2009
DOI: 10.1080/17451590903236741
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic disturbances and plant diversity of the Madhupur Sal forests (Shorea robustaC.F. Gaertn) of Bangladesh

Abstract: and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, re-distribution, re-selling, loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae and drug doses should be independently v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 34 publications
6
57
4
Order By: Relevance
“…Food production and fuel wood production were also strongly preferred, which seems consistent with needs in the densely populated country of Bangladesh (Rahman et al 2009;Dewan and Vacik 2010).…”
Section: Preference Elicitation On Criteria and Indicators For Iwmsupporting
confidence: 53%
“…Food production and fuel wood production were also strongly preferred, which seems consistent with needs in the densely populated country of Bangladesh (Rahman et al 2009;Dewan and Vacik 2010).…”
Section: Preference Elicitation On Criteria and Indicators For Iwmsupporting
confidence: 53%
“…The concept of biodiversity includes diversity at genetic, species, ecosystem and landscape levels, as well as ecological complexes. Due to various human activities resulting in the destruction of habitats, such as deforestation and overexploitation of forest resources, during the last few decades a loss of biodiversity has been reported at a variety of different scales (Trombulak et al 2004;Hooper et al 2005;Fischer and Lindenmayer 2007;Rahman, Ainun, and Vacik 2009). Given this complexity, it is often difficult to judge whether individual forests are being managed in an ecologically sustainable manner (Lindenmayer, Margules, and Botkin 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Firewood is used as one of the main sources of energy for households in rural areas for cooking and heating, as it is the cheapest and most accessible source for the majority of people in developing countries (Shackleton 1993;Badola 1998;Jalilova 2007;Schmidt 2007;Rahman et al 2009). In a recent calculation, it was found that the annual firewood consumption was approximately 5 times higher than the annual increment in Arstanbap (Sorg 2007).…”
Section: Views and Opinions On Biodiversity Lossmentioning
confidence: 99%
“…The Rio Convention of 1992 defined biodiversity as the variety of living organisms at the genetic, species and ecosystem levels and the ecological complexes of which they form a part. Biodiversity is being lost on a local scale due to various human activities such as the destruction of habitats, deforestation and the overexploitation of forest resources during recent decades (Trombulak et al 2004;Hooper et al 2005;Fisher and Lindenmayer 2007;Rahman et al 2009). The conservation of biodiversity can be achieved through active participation of local people, which would allow the gaps between policy and its implementation to be overcome.…”
Section: Introductionmentioning
confidence: 99%